2024
DOI: 10.1001/jamacardio.2023.4664
|View full text |Cite
|
Sign up to set email alerts
|

Decline in Estimated Glomerular Filtration Rate After Dapagliflozin in Heart Failure With Mildly Reduced or Preserved Ejection Fraction

Finnian R. Mc Causland,
Brian L. Claggett,
Muthiah Vaduganathan
et al.

Abstract: ImportanceAn initial decline in estimated glomerular filtration rate (eGFR) is expected after initiating a sodium-glucose cotransporter-2 inhibitor (SGLT2i) and has been observed across patients with diabetes, chronic kidney disease, and heart failure.ObjectiveTo examine the implications of initial changes in eGFR among patients with heart failure with mildly reduced ejection fraction (HFmrEF) or preserved ejection fraction (HFpEF) enrolled in the Dapagliflozin Evaluation to Improve the Lives of Patients With … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Additionally, due to the limited data availability, we could neither analyze eGFR in comparison with mGFR nor extend our evaluation including cystatin-C-based eGFR equations [17,28,29]. Moreover, without in-depth clinical information and repeated sCr measurements, we could not explore the association between eGFR changes and detailed clinical outcomes in various clinical settings [30][31][32][33][34]. Nevertheless, the strength of our study is that the present data were obtained from a large number of enrolled subjects, who reflect the general Korean population.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, due to the limited data availability, we could neither analyze eGFR in comparison with mGFR nor extend our evaluation including cystatin-C-based eGFR equations [17,28,29]. Moreover, without in-depth clinical information and repeated sCr measurements, we could not explore the association between eGFR changes and detailed clinical outcomes in various clinical settings [30][31][32][33][34]. Nevertheless, the strength of our study is that the present data were obtained from a large number of enrolled subjects, who reflect the general Korean population.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, SGLT2 inhibitors have shown promising results in reducing cardiovascular death or HF hospitalisation, as demonstrated in the EMPEROR-preserved study and the DELIVER trial [47][48][49][50][51], especially in patients with mildly reduced or preserved EF, irrespective of their diabetic status. Lastly, vericiguat has demonstrated its efficacy in reducing the combined primary endpoint of cardiovascular death or first HF hospitalisation, albeit less so in patients with an EF percentage between 40 and 45% [52].…”
Section: Pharmacological Treatmentmentioning
confidence: 95%
“…The 2021 ESC guidelines, advocate for a comprehensive pharmacological approach in managing HFmrEF, recommending angiotensin-converting enzyme inhibitors (ACEIs), angiotensin receptor blockers (ARBs) [41], mineralocorticoid receptor antagonists (MRAs) [42], sacubitril/valsartan (ARNIs) [43,44], beta-blockers [45], and sodium-glucose cotransporter 2 inhibitors (SGLT2) [46][47][48][49][50][51] as Class 2b recommendations (Table 1).…”
Section: Pharmacological Treatmentmentioning
confidence: 99%
“…The observed rise in serum creatinine was initially considered a potential safety concern due to the natriuretic and osmotic diuretic effects of SGLT-2i. A secondary analysis of DELIVER examined the implications of the initial decline in eGFR and concluded that it was a frequent observation with dapagliflozin (40% of patients experiencing an initial drop of greater than 10%), but was not associated with subsequent risk of cardiovascular or kidney events [24]. Of note, lack of an adverse impact on the outcomes by the initial dip in eGFR had previously been reported in HF with reduced ejection fraction [25].…”
Section: Gliflozins the Miracle Drugs That Continue To Conquermentioning
confidence: 99%